Building resilience through leadership. Issue 6 (June 2016) - Jagger, Olivia; Lewith, George
Demonstrating leadership skills at work builds resilience by empowering you to take control of your working environment. Demonstrating leadership qualities enables more-effective team-working, which improves your performance and provides a protective support network. Both these processes buffer stress and promote personal resilience. This article explains how you can build personal resilience through leadership and gives advice on ways you can develop both leadership and resilience skills.